STRATEGI PENGEMBANGAN EKOWISATA AIR TERJUN TEMBURUN KECAMATAN SIANTAN TIMUR KABUPATEN KEPULAUAN ANAMBAS PROVINSI KEPULAUAN RIAU - Recsy Poetu Antari; Nurul Qomar; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Temburun Waterfall has the potential that can be developed as ecotourism products to support environmental sustainability, welfare and improving the quality of community life. It takes several alternative strategies in developing the Temburun Waterfall ecotourism by utilizing the strengths owned, minimizing the weaknesses and obstacles and opportunities that exist. This research aims to formulate development strategy of Temburun Waterfall ecotourism. The data used in this research are primary data and secondary data. Primary data obtained from the interview and fill questionnaire by the selected respondents taken using purposive sampling method. Data were analyzed using SWOT analysis. The results showed that the development strategy of Temburun Waterfall ecotourism 1). Strengthening institutions in managing and improving tourism objects and attractions, 2). Offering the potential that exists to outside parties / private sector in order to improve ecotourism development concept ecotourism, 3). Conduct training and assistance on tourism marketing and tourism business development and, 4). Improve the awareness of tourists and the quality of human resources as a reliable tourism activist. Keywords: Development strategy, SWOT analysis, Temburun Waterfall ecotourism